Resource concentration and clustering in replicator dynamics with stochastic reset events - Gómez Garay, Ignacio T.; Zanette, Damian Horacio (Molecular Diversity Preservation International, 2023)
Fil: Gómez Garay, Ignacio T.. Comisión Nacional de Energía Atómica. Gerencia del Área de Energía Nuclear. Instituto Balseiro; Argentina